Human CD8+ T Cells in Asthma: Possible Pathways and Roles for NK-Like Subtypes - Lourenço, Olga; Fonseca, Ana Mafalda; Taborda-Barata, Luis (Frontiers in Immunology, 2016)
Asthma affects approximately 300 million people worldwide and is the most common chronic lung disease, which usually is associated with bronchial inflammation. Most research has focused upon the role of CD4+ T cells and relatively few studies have addressed the phenotypic and functional roles of CD8+ T cell types and subtypes. Human NK-like CD8+ T cells may involve cells that have been described as CD8+CD28-, CD8+CD28-CD57+, CD8+CD27-, or CD8+ effector-memory (TEM) cells, among other. However, most of the data which is available regarding these various cell types were obtained in murine models, did not thoroughly characterize these cells with phenotypically or functionally or did not involve asthma-related settings. Nevertheless, one may conceptualize three principal roles for human NK-like CD8+ T cells in asthma: disease-promoting, regulatory and/or tissue repair. Although evidence for some of these roles is scarce, it is possible to extrapolate some data from overlapping or related CD8+ T cell phenotypes, with caution. Clearly, further research is warranted, namely in terms of thorough functional and phenotypic characterization of human NK-like CD8+ T cells in human asthma of varying severity